Retail Trade as an Agenda-Setting Factor for the Strategic Management of Supply Chains - Olga Demkina; Irina Litvin; Alexander Biryukov; Lesya Bozhko; Ekaterina Vulfovich (International Journal of Supply Chain Management, 2020)
Abstract— The study discusses the impact of effective supply chain management on retail volumes. The features of the logistics development in the Russian Federation are considered. The dependence of the volume of retail commodities (including food products) of the Russian Federation over the past few years on the Logistics Performance Index (LPI) has been presented, and the data obtained have been compared with the survey data on the impact of logistics efficiency on consumer choice. Based on the results of the study, it was found that in Russia there is a direct correlation between retail volumes and Logistic Competence, which is one of Logistics Performance Index components. According to the results of a telephone survey of 158 respondents randomly selected from all regions of the Russian Federation, it was found that at the “customer - commercial enterprise” level, supply chain management efficiency does not affect sales volumes while supply chain inefficiency reduces sales volumes of individual manufacturers. Measures for improving supply chain management at commercial enterprises have been proposed. A mechanism for applying the strategy of integrated logistics outsourcing by a retail trade network has been presented.